2018
DOI: 10.1002/aenm.201803243
|View full text |Cite
|
Sign up to set email alerts
|

Surface State‐Mediated Charge Transfer of Cs2SnI6 and Its Application in Dye‐Sensitized Solar Cells

Abstract: A vacancy‐ordered double perovskite, Cs2SnI6, has emerged as a promising lead‐free perovskite in the optoelectronic field. However, the charge transfer kinetics mediated by its surface state remains unclear. Here, the charge transfer mechanism of Cs2SnI6 is reported and the role of its surface state in the presence of a redox mediator is clarified. Specifically, charge transfer through the surface state of Cs2SnI6 and its subsequent surface state charging are demonstrated by cyclic voltammetry and Mott–Schottk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
32
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 42 publications
3
32
0
Order By: Relevance
“…25,26,27,28,32,34 Our work is in good agreement with those pointing to high bandgap in this range. 25,27,32,34 Regarding the optical bandgap, the photoluminescence (PL) of the thin films results in the emission peak ( Figure 5d) at 792 nm. Translated to energy, this value means 1.57 eV, which matches with the result obtained from the Tauc plot, with a relatively small Stokes shift.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…25,26,27,28,32,34 Our work is in good agreement with those pointing to high bandgap in this range. 25,27,32,34 Regarding the optical bandgap, the photoluminescence (PL) of the thin films results in the emission peak ( Figure 5d) at 792 nm. Translated to energy, this value means 1.57 eV, which matches with the result obtained from the Tauc plot, with a relatively small Stokes shift.…”
Section: Resultssupporting
confidence: 91%
“…Nevertheless, this material itself constitutes a more air stable candidate than its nonoxidized counterpart . It has been previously used as a hole transport layer (HTL) in dye-sensitized solar cells, and also as nanowires or quantum rods . Several synthesis methods have been employed for its preparation. ,, However, the optical properties of this material have not been broadly studied in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…In the seek for the lead-free perovskite materials, Sn-based perovskites have been demonstrated to have a narrower optical bandgap than that of the Pb-based perovskites [26][27][28][29][30] , indicating their larger light absorption range. Especially, all-inorganic Cs 2 SnI 6 perovskite is more preferred material system in view of its good stability, superior conductivity, and appropriate energy band levels [31][32][33][34][35] .…”
mentioning
confidence: 99%
“…[ 92 ] Interestingly, a Cs 2 SnI 6 ‐based regenerator was developed for DSSCs to evaluate the capability of Cs 2 SnI 6 in regenerating oxidized organic dyes. [ 133 ] It was suggested that the highest occupied molecular orbital of the dyes has a strong influence on the performance of the Cs 2 SnI 6 ‐based regenerator. Furthermore, the performance of the Cs 2 SnI 6 ‐based regenerator was compared with a conventional liquid electrolyte.…”
Section: Applications Of Cs2sni6mentioning
confidence: 99%
“…Reproduced with permission. [ 133 ] Copyright 2018, Wiley‐VCH. g) Characteristic J–V and IPCE curves.…”
Section: Applications Of Cs2sni6mentioning
confidence: 99%